(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
Transport-logistics infrastructure is a critical factor in national economic development, ensuring the speed and efficiency of trade operations. Globally, developing transport-logistics systems is considered one of the main avenues for increasing economic efficiency and creating competitive advantages. In Europe and Asia, financial sustainability is a key criterion in financing transport-logistics projects. For instance, in Germany and the Netherlands, projects for the development of railway and port infrastructure are assessed based on financial sustainability indicators, cost optimization, and capital efficiency. Similarly, China’s “Belt and Road Initiative” attracted large-scale investments into transport-logistics networks, establishing a financially sustainable infrastructure model.